Evaluation of Drug Management and Improvement Strategies Using the Hanlon Method in the Pharmacy Installation of Dr. Moewardi General Hospital, Surakarta, Indonesia - Imelia, Lanny; RA.Oetari; Samuel Budi Harsono (Open Access Indonesian Journal of Medical Reviews, 2023)
A hospital pharmacy (FRS) is a unit in a hospital that carries out health efforts by providing quality health services. Medication management in FRS is an important management aspect in achieving service quality. Therefore, IFRS must be managed effectively and efficiently. Inefficiency in use can have a negative impact on hospitals both medically and economically. The aim of this study was to evaluate drug management, including selection, procurement, distribution, and use, based on the 2020 National Formulary standards and improvement strategies using the Hanlon method at the pharmacy installation of Dr. Moewardi General Hospital in 2020. This research is a type of descriptive research with retrospective and concurrent data collection. Data was taken from retrospective data in 2020 and data at the time the research was conducted. Research materials include primary data obtained from observation of research data in the form of document selection, procurement, distribution, and use of medicine in the IFRS Dr. Moewardi General Hospital. Secondary data was obtained from interviews with the head of the pharmacy installation at Dr. Moewardi General Hospital Surakarta, the head of planning, and the head of ULP (procurement services unit). The results of the research show that 1) Medication management in the pharmacy installation at Dr. Moewardi General Hospital Surakarta is not yet efficient at this stage of selection. It is known that the availability of existing medicines does not comply with FORNAS standards in 2020. then, in stage procurement, there is 1 out of 5 indicators that meet the standard; in stage distribution, 5 indicators were obtained, or all of them were not standard, and in staged use, it was found that 1 of the 5 indicators met the standard. 2) The improvement strategy uses the Hanlon method in drug management, namely prioritizing problem repairs sequentially, starting from the percentage of conformity with the number of drug items available with FORNAS to the number of drug items per prescription sheet.